2023
DOI: 10.7759/cureus.34856
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Awake Abdominal Surgery Under Thoracic Epidural Anaesthesia in a High-Risk Patient Within a Resource-Limited Setting

Abstract: Awake abdominal surgery is performed daily around the world for caesarean section surgery under lumbar subarachnoid anaesthesia and/or graded lumbar epidural anaesthesia. Reports of awake abdominal surgery under thoracic epidural anaesthesia (TEA) for patients with bowel obstruction are scarce, as this patient population is at high risk for pulmonary aspiration. In this report, we describe a case in which a graded TEA was successfully used as the sole anaesthetic technique in a patient with severe pulmonary di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A recent publication showed that thoracic epidural anaesthesia could be another feasible option for patients with severe pulmonary disease requiring an awake emergency laparotomy for bowel ischaemia in the absence of postoperative intensive care monitoring [39]. Though this is certainly an interesting alternative to general anaesthesia and NA, the article is only a single patient case study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication showed that thoracic epidural anaesthesia could be another feasible option for patients with severe pulmonary disease requiring an awake emergency laparotomy for bowel ischaemia in the absence of postoperative intensive care monitoring [39]. Though this is certainly an interesting alternative to general anaesthesia and NA, the article is only a single patient case study.…”
Section: Discussionmentioning
confidence: 99%